Hydrological Processes of Coconut Palm Plantation: Rainwater uptake, Return to the Atmosphere, and The Moisture Conservation - Teuku Achmad Iqbal (Buletin Palma, 2008)
The hydrological processes of coconut palm plantation are briefly reviewed in order to describe their role to provide sustainable way to improve coconut productivity. This review is based upon two distinct influence of coconut plantation on hydrological processes: the impact of coconut palm physiology on rainwater uptake and return to the atmosphere, and the moisture conservation to control runoff. To fully understand relationship between rainfall and coconut plantation, the interception, stemflow, and throughfall patterns are reviewed. Evapotranspiration is used as the indicators to describe potential changes in storage. Insufficient moisture in the soil will reduce nutrient absorption resulting in poor growth in young palms and low nut production. Therefore, some practices are introduced in this paper to maximize the volume of rainwater to be absorbed into the soil sub layers without allowing it to run-off the coconut plantation land.